Yielding of biomass, essential oil, contents phosphorus and potassium of Justicia pectoralis var. stenophylla in response to the fertilization organic and mineral. - Bezerra, Antonio (2008)
“Chambá” (Justicia pectoralis var. stenophylla) is a traditional medicinal herb widely used in the North and Northeast regions of Brazil to treat asthma, cough and bronchitis. Agronomical studies about the organo-mineral fertilization of this species are rare. To overcome this deficiency an essay over alluvial soil was performed at the Núcleo de Plantas Aromáticas e Medicinais – Universidade Federal do Piauí. The treatments correspondent to six doses of organic fertilizer (0; 10; 20; 30; 40 and 50 t.ha-1) combined with three N-P2O5-K2O formulations (0-0-0; 40-200-120 and 80-120-240 kg.ha-1) were disposed over subdivided parcels in random blocks with four replications. The seedlings were obtained by cutting. They were transplanted to garden beds aging 31 days and spaced 0.25 x 0.30 m. The evaluated features were: plant height, dry weight of the aerial part, P and K content and essential oil yielding. The results showed that the organic and mineral fertilizations did not affect the growth of the plant, biomass production and contents of P and K of the aerial part of the plant. The essential oil yielding presented a trend of decrease with the increasing doses of bovine manure in each N-P2O5-K2O formulation.